2022
DOI: 10.1080/21645515.2022.2091898
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy and acceptance among the public in the Gulf Cooperation Council countries: A review of the literature

Abstract: Vaccine hesitancy has a significant impact on tackling infectious diseases as it has resulted in reemergence of vaccine-preventable diseases. This review aims to provide an up-to-date evaluation of COVID-19 vaccine hesitancy among the public in the Gulf Cooperation Council countries. We searched the PubMed and SCOPUS databases for manuscripts published on vaccine hesitancy and/or acceptance among the public in GCC countries up till April 1 st , 2022. Forty-nine studies met the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Data from 32 previous surveys showed different hesitancy rates to receive COVID-19 vaccine ranging from 5% to 82% in Saudi Arabia ( Alsalloum et al, 2022 ). Most of the studies (n=26) with a total population of 37,326 people reported a hesitancy rate of at least 21%, whereas the remaining 6 studies with a total population of 5,115 people showed a hesitancy rate of ≤ 16%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data from 32 previous surveys showed different hesitancy rates to receive COVID-19 vaccine ranging from 5% to 82% in Saudi Arabia ( Alsalloum et al, 2022 ). Most of the studies (n=26) with a total population of 37,326 people reported a hesitancy rate of at least 21%, whereas the remaining 6 studies with a total population of 5,115 people showed a hesitancy rate of ≤ 16%.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, at least 21 of the 32 surveys were conducted after the vaccine rollout in the country in January 2021, five of which were among the studies that showed low hesitancy rate (four of 32 studies did not specify the study period). Based on these previous studies from Saudi Arabia, the most common predictors of vaccine hesitancy showing significant association with the decision of not receiving the vaccine were low to moderate perceived severity of COVID-19, concerns about vaccine safety and efficacy, negative behavior regarding vaccines in general, lower educational level, belief in conspiracy theories, and accepting that natural immunity is sufficient (some respondents also had a history of contracting the infection) ( Alsalloum et al, 2022 ). These factors were prevalent in the surveys that were done before and after the vaccine rollout.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations